Elastic properties of ribosomal RNA building blocks: molecular dynamics of the GTPase-associated center rRNA - Rázga, Filip; Koca, Jaroslav; Mokdad, Ali; Sponer, Jirí (Nucleic acids research, 2007)
Explicit solvent molecular dynamics (MD) was used to describe the intrinsic flexibility of the helix 42-44 portion of the 23S rRNA (abbreviated as Kt-42+rGAC; kink-turn 42 and GTPase-associated center rRNA). The bottom part of this molecule consists of alternating rigid and flexible segments. The first flexible segment (Hinge1) is the highly anharmonic kink of Kt-42. The second one (Hinge2) is localized at the junction between helix 42 and helices 43/44. The rigid segments are the two arms of helix 42 flanking the kink. The whole molecule ends up with compact helices 43/44 (Head) which appear to be modestly compressed towards the subunit in the Haloarcula marismortui X-ray structure. Overall, the helix 42-44 rRNA is constructed as a sophisticated intrinsically flexible anisotropic molecular limb. The leading flexibility modes include bending at the hinges and twisting. The Head shows visible internal conformational plasticity, stemming from an intricate set of base pairing patterns including dynamical triads and tetrads. In summary, we demonstrate how rRNA building blocks with contrasting intrinsic flexibilities can form larger architectures with highly specific patterns of preferred low-energy motions and geometries.
Keywords: Molecular Sequence Data; konformace nukleové kyseliny; Models, Molecular; Nucleic Acid Conformation; Computer Simulation; počítačová simulace; RNA, Ribosomal, 23S; Ions; ionty; Base Sequence; sekvence nukleotidů; konzervovaná sekvence; párování bází; molekulární modely; RNA, Archaeal; pohyb těles; RNA ribozomální 23S; Motion; Base Pairing; archeální RNA; molekulární sekvence - údaje; Conserved Sequence; Haloarcula marismortui